Maternal Neurotic Anxiety in the film Run (2020): A Psychoanalysis Study of Diane’s Character - Satria Utina; Magdalena Baga; Rusni Podungge (BULLET : Jurnal Multidisiplin Ilmu, 2026)
Anxiety manifests through excessive and uncontrolled emotions, as well as manipulative behavior. This is caused by intense internal and external conflicts. This study aims to show how films can represent the dynamics of the human psyche and broaden our understanding of the relationship between psychological trauma and anxiety disorder in fictional characters. Using Sigmund Freud's psychoanalysis approach, this study examines the things that can trigger neurotic anxiety in characters in films. The character Diane is not the main character in the film Run (2020), but she is at the center of all the problems that arise for the main character, Chloe. She is depicted as a very protective and impulsive mother towards her daughter, Chloe, who suffers from an illness that causes a disability. The theory used in this study is Freud's theory of personality structure, which includes the id, ego, and superego. This theory is used to analyze data obtained through observations of the script and film. The results of the study show that Diane's neurotic anxiety is triggered by the death of her biological baby and the fear of losing her mother figure, as well as a subconscious urge to act contrary to her reality as a mother.